Correlation Between Early Marriage And Family Income With The Incidence Of Stunting At Kamaipura Community Health Center - Putri Wilda Natasya; Ni Nyoman Elfiyunai; Sintong H. Hutabarat (Universitas Widya Nusantara, 2025)
Background: Stunting is a condition where a child's height is shorter than the standard for their age due to multifactorial factors such as. Early marriage is a phenomenon that still occurs a lot, where early marriage can trigger stunting. The incidence of stunting is also related to low socio-economic. Objective: To analyze the relationship between early marriage and family income with the incidence of stunting at the Kamaipura Health Center. Method: This type of research is quantitative with a cross-sectional approach. The population is all mothers who have toddlers aged 12-59 months totaling 325, with a purposive random sampling technique. The number of samples is 180. Research Results: The results showed that out of 180 respondents, those who did not marry early were more, those who had family income ≥ UMK Sigi Regency were more, and the incidence of stunting toddlers was higher. The results of the chi-square statistical test of the relationship between early marriage and stunting incidence p value = 0.0871 (p>0.05), and the relationship between family income and stunting incidence p value = 0.0983 (p>0.05) Conclusion: There is no Correlation between early marriage and family income with stunting incidence at the Kamaipura Health Center. Suggestion: For the Kamaipura Health Center, the results of this study can be a source of information, so that the Health Center can conduct further analysis to identify other factors that play a role in stunting incidence.